Civil wars in the Democratic Republic of Congo, 1960-2010 - Kisangani, Emizet F. (Lynne Rienner Publishers, 2012)
Wars of secession, ethnic wars, rebellions, mutinies, and Congolese-led invasions have been part of the political landscape of the Democratic Republic of Congo since the country became independent in 1960. Why? And what can we learn from this seemingly unending series of internal conflicts? Emizet François Kisangani explores these fundamental questions within a rigorously systematic and uniquely comprehensive framework. Looking closely at five decades of civil wars in the DRC, Kisangani finds ample evidence to challenge popular paradigms. His focus on the politics of exclusion and his attention to both the micro- and macroprocesses of the wars provides an analytical lens through which not only the nature of civil wars, but also Congoʹs politics more broadly, are brought into clearer focus. -- Publisher description.